Increase the level of environmental safety for mechanical ventilation of light-oil storage tanks - Гарбуз, Сергей Викторович (Technology audit and production reserves, 2015)
This paper evaluated the environmental risk of degassing light oil-storage tank, by quantifying emissions of hydrocarbon vapors in the air. To determine the basic parameters of the degassing tank that is carried out by mechanical ventilation, it has been created test bench geometrically similar to RVS-5000. Based on theoretical and experimental data, it is calculated the concentration of harmful substances (hydrocarbons) in the air for degassing method using in Ukraine, at all stages. Based on international experience, it is shown the need for hydrocarbon vapor recovery units, as in the current operation, and during the full decontamination. An analysis of existing and exploited in various countries systems for vapor recovery of hydrocarbons is conducted. The presence of the aerodynamic resistance in plants for hydrocarbon vapor recovery does not allow degassing tank using in Ukraine under the current regulations of the degassing process. To improve the environmental safety of the degassing process of tanks, taking into account the need for a filtration system to trap hydrocarbon vapors and increase the overall efficiency of the degassing tank, it is proposed a fundamentally new ejector-vortex method of supplying fresh air into the space of the tank, based on which the new technology of mechanical ventilation of tanks was created.